An Analysis of Two Albertan Anti-Domestic Violence Public Service Campaigns: Governance in Austere Times - Gerrits, Bailey (Atlantis)

(untitled) (Mount Saint Vincent University, 2017)
This article compares two anti-domestic violence campaigns created by the Edmonton Police Services and the Government of Alberta. This paper argues that both campaigns rely on and reinforce gendered and racialized schema, legitimize each institution, and simultaneously call upon you, the viewer, to address domestic violence.